2020
DOI: 10.1007/s11469-020-00416-8
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful Living to Promote Complete Mental Health Among University Students in the Context of the COVID-19 Pandemic

Abstract: Maintaining positive mental health can be challenging during the COVID-19 pandemic which undoubtedly caused devastating consequences on people’s lives. There is need to determine factors contributing to mental health of people during the pandemic. The current study aims to examine the effect of meaning in life on complete mental health, which represents the presence of positive functioning and the absence of psychopathological symptoms. The participants of the study included 392 (70.9% female) undergraduate st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 68 publications
2
72
0
4
Order By: Relevance
“…A high level of coronavirus is diminished by meaning in life, which in turn leads to greater satisfaction with life. Extant studies have confirmed the positive relationships between meaning in life and satisfaction with life (García-Alandete, 2015 ; Arslan et al, 2020a ; Yildirim et al, 2020a ; Arslan and Yildirim, 2021 ). To the best of our knowledge, no previous study has examined the underlying relations among coronavirus suffering, meaning in life, and satisfaction with life in the context of the current pandemic.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…A high level of coronavirus is diminished by meaning in life, which in turn leads to greater satisfaction with life. Extant studies have confirmed the positive relationships between meaning in life and satisfaction with life (García-Alandete, 2015 ; Arslan et al, 2020a ; Yildirim et al, 2020a ; Arslan and Yildirim, 2021 ). To the best of our knowledge, no previous study has examined the underlying relations among coronavirus suffering, meaning in life, and satisfaction with life in the context of the current pandemic.…”
Section: Discussionmentioning
confidence: 91%
“…Individuals with high levels of stressrelated growth are less vulnerable to coronavirus suffering and report greater meaning in life and satisfaction with life. Previous studies have demonstrated that the experience of stressors would reduce a person's resilience and the sense of meaning in life in the face of traumatic events (Yildirim et al, 2020a(Yildirim et al, , 2021. Stress-related growth is related to positive states of mind, and it has benefits for individuals who experience it, including both positive changes in personal resources such as mastery and better psychological adjustment following the traumatic events (Park and Fenster, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations